1997
DOI: 10.1007/bf02867955
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the canine cardiac sarcolemma in experimental myocardial ischemia

Abstract: The cardiac sarcolemma was characterized in 13 normal and 11 ischemic dog hearts by enzyme analysis and compositional assays. Significant decreases in the activities of the sodium-potassium and calcium pumps and structural compositional disturbances were observed in ischemia. High concentrations of oleic acid, a fatty acid and palmitoyl carnitine, a fatty acid intermediate caused inhibition of the enzyme pump activities of the normal sarcolemma. Thus, ischemia results in the functional impairment of the sarcol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…On the other hand, Netticadan et al . () reported no change in canine cardiac sarcolemmal cholesterol levels with ischaemia, while phospholipids (primarily phosphatidylcholine and phosphatidylethanolamine) were significantly depleted. They also observed a general increase in fatty acid unsaturation following myocardial ischaemia.…”
Section: Sarcolemmal Makeup Changes With Age and Diseasementioning
confidence: 94%
“…On the other hand, Netticadan et al . () reported no change in canine cardiac sarcolemmal cholesterol levels with ischaemia, while phospholipids (primarily phosphatidylcholine and phosphatidylethanolamine) were significantly depleted. They also observed a general increase in fatty acid unsaturation following myocardial ischaemia.…”
Section: Sarcolemmal Makeup Changes With Age and Diseasementioning
confidence: 94%
“…Two additional runs for each system were conducted up to 300 ns (replica 2 and replica 3). In all systems, DPPC was the phospholipid used in the membrane bilayer, because phosphatidylcholines (PCs), especially those bearing oleic, linoleic or palmitoyl alkyl chains are the most abundant lipid species found in the plasma membranes, vascular smooth muscle cells [34] and sarcolemma cardiac membranes, while 40 mol% cholesterol was added in order to simulate the natural cholesterol percentage of the sarcolemma membranes, where AT1R is naturally expressed [35] . In all systems, the inactivated form of AT1R was used with PDB ID: 4YAY [36] .…”
Section: Methodsmentioning
confidence: 99%
“…Phosphatidylcholines (PCs) are the most abundant lipid species in the plasma membranes of the vascular smooth muscle cells [17] and sarcolemma cardiac membranes but also other kinds of lipids play a significant role in the membrane functionality [18]. The most frequently found PCs consist of oleic, linoleic and dipalmitoyl alkyl chains.…”
Section: Introductionmentioning
confidence: 99%
“…Their dynamic and thermotropic properties have been studied using a variety of physical chemical techniques [1927] and Molecular Dynamics (MD) simulations [28]. These studies revealed also that their ARB partition coefficient in the fluid state resembles that of natural plasma membranes of the vasculature [17,18]. Briefly, the phosphatidylcholine bilayers at low temperatures occur in the lamellar gel phase (L β ) and at higher temperatures in the liquid-crystalline phase (L α ).…”
Section: Introductionmentioning
confidence: 99%